1983
DOI: 10.1037/0278-7393.9.4.747
|View full text |Cite
|
Sign up to set email alerts
|

Encoding effort and recall: A cautionary note.

Abstract: In the five experiments reported here we attempted to demonstrate an effect on item memorability of the amount of effort expended during the encoding process. The encoding task in two experiments was anagram solving; here, solution difficulty was varied. In the third experiment, subjects were required to judge whether a word fit meaningfully into a sentence frame, arid the ease of making this decision was manipulated. The final two experiments involved picture naming under time pressure; pictures were displaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…Both experiments replicate the results of Zacks et al (1983) in demonstrating that the effort involved in solving difficult anagrams exceeds that involved in solving easy anagrams. Furthermore, recall of solutions to difficult anagrams did not exceed that for easy ones (Experiment I).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Both experiments replicate the results of Zacks et al (1983) in demonstrating that the effort involved in solving difficult anagrams exceeds that involved in solving easy anagrams. Furthermore, recall of solutions to difficult anagrams did not exceed that for easy ones (Experiment I).…”
Section: Discussionsupporting
confidence: 78%
“…Solution time is a measure of anagram difficulty (Mayzner & Tresselt, 1958;Zacks et al, 1983). An analysis of variance (ANaYA) showed that mean response times varied with condition [F(2,33) = 52.13, p < .001; see Table I].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, how does effort after meaning relate to the cognitive effort required to perform other encoding tasks, such as item generation, semantic elaboration, or anagram problem solving (e.g., Craik & Tulving, 1975;Jacoby, 1978;Slamecka & Graf, 1978;Tyler, Hertel, McCallum, & Ellis, 1979)? The latter question is underscored by the fact that cognitive effort is poorly understood in general, and prior research examining the effects of cognitive effort on memory performance has yielded mixed results (Ellis, Thomas, & Rodriguez, 1984;Zacks, Hasher, Sanft, & Rose, 1983).…”
Section: Effort After Meaning and Generationmentioning
confidence: 99%